1996
DOI: 10.1038/383076a0
|View full text |Cite
|
Sign up to set email alerts
|

A neuronal learning rule for sub-millisecond temporal coding

Abstract: A paradox that exists in auditory and electrosensory neural systems is that they encode behaviorally relevant signals in the range of a few microseconds with neurons that are at least one order of magnitude slower. The importance of temporal coding in neural information processing is not clear yet. A central question is whether neuronal firing can be more precise than the time constants of the neuronal processes involved. Here we address this problem using the auditory system of the barn owl as an example. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
996
0
12

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,063 publications
(1,032 citation statements)
references
References 26 publications
24
996
0
12
Order By: Relevance
“…An influence of the temporal signal order on plasticity was proposed by Gerstner et al (1996) and experimentally confirmed by Markram et al (1997), Magee and Johnston (1997), and Bi and Poo (1998) [although Levy and Steward (1983) had already discovered this phenomenon]. These authors found that for the expression of LTP or LTD not only the activity as such matters but also the timing.…”
Section: Long-term Plasticitymentioning
confidence: 87%
“…An influence of the temporal signal order on plasticity was proposed by Gerstner et al (1996) and experimentally confirmed by Markram et al (1997), Magee and Johnston (1997), and Bi and Poo (1998) [although Levy and Steward (1983) had already discovered this phenomenon]. These authors found that for the expression of LTP or LTD not only the activity as such matters but also the timing.…”
Section: Long-term Plasticitymentioning
confidence: 87%
“…Excitatory synapses from adaptable inputs are represented by weighted excitatory postsynaptic potential waveforms, (t n ). The weighting factors, w A (t n ), change in t n as the system adapts due to a learning rule that depends on the relative timing of pre-and postsynaptic spikes [5]. The contribution of adaptable inputs to the neuron's membrane potential is given by, V A (t n ) = m w A m (t n ) (t n − t m ).…”
Section: Methodsmentioning
confidence: 99%
“…where T is a suitably chosen timescale, the angle brackets show a temporal average over t ′ centred around time t, and H ab (τ ) describes the STDP function, fitted with two exponentials which depend on the post-synaptic neuron [1,20,13,14]:…”
Section: Changes In Synaptic Weightsmentioning
confidence: 99%
“…By the same token, the method will be appropriate to cases where large numbers of neurons are stimulated simultaneously, as in TMS. Recently, Robinson [36] has assembled a simple numerical model of spike-timing dependent plasticity (STDP) [1,20,13,14] within neurons that builds upon the platform of neural field modelling. This allowed a first application of a neural field model to TMS.…”
Section: Introductionmentioning
confidence: 99%